Pluralism, Liberalism, and Islamism: Religious Outlook of Muhammadiyah - Ahmad Najib Burhani (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2018)
Muhammadiyah has been perceived as an example of a successful blend between Islam and modernity. By adopting modern spirit of discipline, equality, and a hard work ethics, this organization has become a vibrant and independent movement. The number of Muhammadiyah educational and health institutions is only surpassed by those owned by the Indonesian government. Muhammadiyah has 177 universities; thousands of secondary, middle, and elementary schools, as well as hundreds of hospitals and other health institutions. However, the organization’s successes in social, educational, and economic do not necessarily indicate that it also embraces pluralistic values and religious tolerance. This paper, therefore, intends to describe Muhammadiyah’s position in the context of pluralism, liberalism, and Islamism. It argues that although Muhammadiyah is predominated by members with moderate religious inclinations, but a significant number of them are exclusively puritan in their theology. The organization’s focus on social services is the reason why Muhammadiyah has evaded Islamist tendencies.